Exploring ethnomathematics in Malay architecture and traditional hall in Penyengat Island and connecting it to geometry in elementary schools - Fadhillah , Rizki Rahmali; Putra, Zetra Hainul; Zufriady; Jismulatif; Aljarrah, Ayman (Jurnal Elemen, 2025)
Malay ethnomathematics is culture-based learning that is very important in 21st-century life. The progress of globalization has led to many technological advances, which have resulted in many cultures being abandoned or even extinct. Ethnomathematics research can be a solution for preserving culture, because it integrates culture and learning materials in schools. This study aims to explore Malay ethnomathematics in the architecture of the Indra Perkasa Traditional Hall on Penyengat Island as a resource for teaching mathematics on geometry and measurement in elementary schools. The method used was an ethnographic study, which is part of a qualitative research method. Data collection techniques included observation, interviews, documentation, and other sources, such as books and journals. This study shows some aspects of Malay ethnomathematics related to geometry and measurement materials in elementary schools, including flat shapes, spatial shapes, and length measurements. This study indicates the potential for the integration of Malay ethnomathematics into the architecture of the Indra Perkasa Traditional Hall on Penyengat Island as a mathematics learning resource for geometry and measurement in elementary schools in Indonesia.